Popular practices, narrative fictions and philosophical reflection in Latin America - Rubio Ángulo, Jaime (Estudios de Filosofía, 1990)
Latin American Philosophy is for me an expression that describes a style of reflection, that is, the way the philosopher responds to the demands of his situation with the elements that he has ’at hand’ by understanding, that is, creating projects.